2008
DOI: 10.1121/1.2816573
|View full text |Cite
|
Sign up to set email alerts
|

Auditory-visual speech perception in normal-hearing and cochlear-implant listeners

Abstract: The present study evaluated auditory-visual speech perception in cochlear-implant users as well as normal-hearing and simulated-implant controls to delineate relative contributions between sensory experience and cues. Auditory-only, visual-only, or auditory-visual speech perception was examined in the context of categorical perception, in which an animated face mouthing /ba/, /da/, or /ga/ was paired with synthesized phonemes from an 11-token auditory continuum. A 3-alternative, forcedchoice, method was used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
81
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(101 citation statements)
references
References 79 publications
19
81
1
Order By: Relevance
“…The present results confirmed the previous findings that CI users compensatively use lip-reading to improve speech perception (Kaiser et al, 2003;Rouger et al, 2007Rouger et al, , 2008Desai et al, 2008). The present CI users showed significantly improved word perception performances in all of the quiet and noise conditions in comparisons between the AO and AV conditions.…”
Section: Methodssupporting
confidence: 95%
See 1 more Smart Citation
“…The present results confirmed the previous findings that CI users compensatively use lip-reading to improve speech perception (Kaiser et al, 2003;Rouger et al, 2007Rouger et al, , 2008Desai et al, 2008). The present CI users showed significantly improved word perception performances in all of the quiet and noise conditions in comparisons between the AO and AV conditions.…”
Section: Methodssupporting
confidence: 95%
“…The present CI users showed significantly improved word perception performances in all of the quiet and noise conditions in comparisons between the AO and AV conditions. As has been argued in previous studies (Kaiser et al, 2003;Desai et al, 2008), the present CI users used lip-reading despite having more than 2 years of CI use.…”
Section: Methodsmentioning
confidence: 50%
“…The McGurk effect is more induced as age increases [9,20]. The patients using CI showed stronger reliance on visual cues than those of normal-hearing controls by the McGurk stimuli [21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies with the McGurk stimuli have shown similarities in the perception of incongruent audiovisual information in patients with CI and individuals with normalhearing [21][22][23][24]. Desai et al [21] evaluated postlingually deafened English-speaking adult CI users and normal-hearing controls with the McGurk stimuli, and found that CI users showed strong reliance on visual cues whereas normal-hearing controls showed reliance on auditory cues. Rouger et al [22] investigated the McGurk effect in adult French patients and reported that those with CI continued to maintain strong lip reading abilities.…”
mentioning
confidence: 98%
See 1 more Smart Citation